TOWARDS AN INCLUSIVE LEARNING ENVIRONMENT: EDUCATIONAL SEMINAR ON THE IMPLEMENTATION OF CHILD WELFARE LAW IN SCHOOLS: MENUJU LINGKUNGAN BELAJAR YANG INKLUSIF: SEMINAR PENDIDIKAN TENTANG IMPLEMENTASI UU KESEJAHTERAAN ANAK DI SEKOLAH - Mardiyati; Sulasti; Yualiana, Ana; Rahmat, Didi; Wahyudi, Hijrah (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
Community service activities in the form of a one-day seminar with students from SDIT Haruniyah residing in East Pontianak, West Kalimantan Province. The activity took place on December 15, 2023. The participants of the activity were all parents of the students and the academic community of SDIT Haruniyah. The implementation of the Community Service Activity that has been held is a step towards implementing the child-friendly school program at the school unit level. The method of the activity was conducted through counseling to provide brainstorming related to the implementation of Child-Friendly Schools. The participants of the activity were school principals, teachers, and parents who came from SDIT Haruniyah in East Pontianak. The result of the activity is the distribution of knowledge related to the Child-Friendly City Policy and the Child-Friendly School program to fulfill the rights and prioritize the rights of children (PUHA) at the school unit level.